Penerapan Metode Course Review Horay Untuk Meningkatkan Minat Belajar Mahasiswa Prodi Pendidikan Biologi Universitas Bengkulu - Nike Anggraini (Universitas Islam Negeri Mataram, 2017)
The Purpose of this study is to determine the use of Course Review Horay method for increasing students interest in Vertebrate Zoology courses in Biology Education Department year 2017/2018. This study is a Classroom Action Research, the subjects consisted of 47 students. Data were collected using observation, questionnaires, and documentation. Data obtained were analyzed using descriptive analysis and effect size. This study was conducted in three cycles, each consisting of one meeting during 2 x 50 minutes. Result showed that the Course review horay method could increase students’ interest and the cognitive learning outcomes. Based on questionnaires on students learning interest, at cycle I, data obtained as much as 44,73%, while at cycle II showed an increase in average score by 81,58%. As for the cognitive learning outcomes showed an increase in post-test value in each cycle. The effect size between cycle I and cycle II as much as 0.39 representing small effect size. While the effect size for cycle II and III were 1, 78 which represent high effect size.